Investigating the Offending Histories of Undocumented Immigrants - Bersani, Bianca; Fine, Adam D.; Piquero, Alex R.; Steinberg, Laurence; Frick, Paul J.; Cauffman, Elizabeth (Migration Letters, 2018)
This study investigates the association between undocumented immigration and crime among youthful offenders. Using official record and self-reported offending measures collected across seven-waves of data from the longitudinal Crossroads Study, the prevalence and variety of offending are compared for undocumented immigrant, documented immigrant, and US-born groups during the transition into young adulthood. Results suggest that, as compared to documented immigrants and US-born peers, undocumented immigrants report engaging in less crime prior to and following their first arrest. Conversely, official records reflect a marginally higher level of re-arrest among undocumented immigrants, particularly in the months immediately following the first arrest. This divergence in findings warrants focused consideration to disentangle whether the difference is due to differential involvement in crime, differential treatment in the justice system, or a combination of factors. Additional research is needed to test whether the results found in this study generalize to other immigrant groups and contexts.